Motives of Peer Support Volunteers with Experiences of Mental and Addictive Disorders: An Innovative Approach in the Context of Employment Promotion in Germany - Klara Lammers; Gudrun Dobslaw; Michael Stricker; Johannes Wegner (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2022)
Peer support approaches are gaining increasing importance within the mental health sector as an effective way to assist people with mental and addictive disorders. This article explores peer support volunteers' motives for voluntary engagement in a model project in Germany. It aims to gain a deeper understanding of peer support approaches and their underlying motivations in an innovative context. Twenty-three qualitative interviews with peer support volunteers were analyzed according to Mayring's qualitative content analysis. Results showed that voluntary engagement fulfills a heterogeneous range of functions for peer support volunteers. Alongside "typical" volunteers' motives, there were peer-specific functions such as motivation due to own personal experiences and the objective of changing societal attitudes toward mental health. Furthermore, the context of employment promotion played a motivational role: Many interview partners aimed to transform counseling structures within the institutions they had experienced as clients themselves.
Keywords: 300; Peer support; Voluntary work; Motivation; Employment promotion; Mental health